PROJECT PENETASAN TELUR AYAM TERHADAP HASIL BELAJAR IPA PADA SISWA TUNAGRAHITA RINGAN - PUSPA AMBARWATI, TALITHA; RIANTO, EDY (Jurnal Pendidikan Khusus, 2019)
The ability of mentally retardation children in mastering learning the material of animal breeding was still difficult so that it influenced the learning result value which was less satisfied with the average value 50 or under KKM value. This research had purpose to know the influence of the project of hatching chicken eggs toward learning science result to mild mentally retardation students. This research used quantitative approach, pre-experiment kind with One group pre test ? post test design. The average value of pre test result indicated score 37.5 and the average value of post test result got 76.2. The treatment was done 8 times meeting. Student ADT got the highest value and student SI got the lowest value. The research result obtained stated that there was influence of the project of hatching chicken eggs toward learning science result to mild mentally retardation students significantly with the result: Z counted = 2,52 was greater than Z table = 1,64, critic value 5%. In this way, the project of hatching chicken eggs could be effective to be applied to support the learning result of mild mentally retardation students. Keywords: learning science result, the project of hatching chicken eggs, mild mentally retardation